HUBUNGAN INDEKS MASSA TUBUH DENGAN TEKANAN DARAH TINGGI PADA LANSIA DI DESA X - Jalillah, Siti; Mailani, Rena; Faradillah, Kiki Rezki; Oktarina, Mona (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Background : High blood pressure is the biggest global disease in 2015 and one of the factors causing premature death. High blood pressure is influenced by various factors such as age, stress, lifestyle and diet. People with poor eating patterns will result in the accumulation of fat in the body which will result in excess BMI or what is called obesity. The accumulation of fat will cause blockages in the blood vessels. According to 2018 Riskesdas statistics, there are 21.8 percent of obesity sufferers in Indonesia. Methods : This research uses a quantitative descriptive research design with a cross-sectional approach. With a sample of 92 elderly people and with an error rate of 0.05. This research was carried out offline using a sphygmomanometer and screening sheet. Results : The highest body mass index was in the obesity category with a percentage of 47.8% and the highest high blood pressure value was in the stage I high blood pressure category with a percentage of 77.2%. After the correlation test, it was found that there was no relationship between body mass index and high blood pressure, with p=0.153 p(<0.05). Conclusion : There is no relationship between body mass index and high blood pressure. Keywords: Hypertensi; Body Mass Indeks; Elderly; Physiotherapy